Angiotensin converting enzyme I/D, angiotensinogen T174M-M235T and angiotensin II type 1 receptor A1166C gene polymorphisms in Turkish hypertensive patients - (:unkn) unknown (NATURE PUBLISHING GROUP, 2003)
Essential hypertension is a multifactorial disease in which genetic and enviromental factors play an important role. These factors differ in each population. As there are no existing data for the Turkish population, we investigated four Renin Angiotensin System (RAS) gene polymorphisms, the anglotensin converting enzyme (ACE), angiotensinogen (AGN) M235T/T174M and angiotensin II type 1 receptor A1166C polymorphism in 109 hypertensive and 86 normotensive Turkish subjects. Polymerase Chain Reaction (PCR) and Restriction Fragment Length Polymorphism (RFLP), and agarose gel electrophoresis tecniques were used to determine these polymorphism. The frequencies of person that carry ACE D allel (DD+ID) was significantly higher in hypertensive group (99.1%) than controls (80%) (P < 0.000). M235T TT genotype was also found significantly higher in hypertensives than control group (20% vs 2.7%; P < 0.001). The frequency of AGN 174M allele was higher in the hypertensive group than control subjects (8.76% vs 4.81%). Frequency of ATR1 C allele (AC+CC genotypes) was found higher hypertensives than controls (39.4% vs 25.9%; P = 0.054). Our results suggest that an interact ion exists, between the RAS genes and hypertension in Turkish population.
Keywords: A1166C; angiotensin converting enzyme; angiotensinogen; hypertension M325T; polymorphism; T174M; INSERTION DELETION POLYMORPHISM; BLOOD-PRESSURE; MET(235)->THR VARIANT; RAPID DETECTION; ASSOCIATION; RISK; LINKAGE; SYSTEM; ALLELE; LOCUS